2022
DOI: 10.1093/cercor/bhac318
|View full text |Cite
|
Sign up to set email alerts
|

Temporal origin of mouse claustrum and development of its cortical projections

Abstract: The claustrum is known for its extensive connectivity with many other forebrain regions, but its elongated shape and deep location have made further study difficult. We have sought to understand when mouse claustrum neurons are born, where they are located in developing brains, and when they develop their widespread connections to the cortex. We established that a well-characterized parvalbumin plexus, which identifies the claustrum in adults, is only present from postnatal day (P) 21. A myeloarchitectonic out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 72 publications
0
22
1
Order By: Relevance
“…We performed unilateral injections of retro-AAV-CAG-GFP into the RSC of adult mice (>P70) and analyzed GFP expression in the claustrum 14 days post injection ( Figure 1A-C ). Several studies found Nurr1 to be a relatively selective marker for the claustrum at different ages and across different species, including rodents and primates (10,11,13,20). We found that Nurr1 immunolabelling showed a dense population of cells that appeared to be spatially aligned with the GFP-labeled retro-RSC central zone ( Figure 1C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…We performed unilateral injections of retro-AAV-CAG-GFP into the RSC of adult mice (>P70) and analyzed GFP expression in the claustrum 14 days post injection ( Figure 1A-C ). Several studies found Nurr1 to be a relatively selective marker for the claustrum at different ages and across different species, including rodents and primates (10,11,13,20). We found that Nurr1 immunolabelling showed a dense population of cells that appeared to be spatially aligned with the GFP-labeled retro-RSC central zone ( Figure 1C, D ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar experiments performed on rats observed that claustral populations are produced between E11.5 and E14.5 with a peak at E12.5 (22). The most recent study by Hoerder-Suabedissen (34) on neurogenesis of the claustrum in mice indicated that claustrum neurons were born at a short time window, E12.5 and neurons in endopiriform nucleus were born at E11.5. Here we found that claustrum neurons in macaques are generated later than subplate neurons of the insular cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebral delivery of viral vectors was performed as previously described . In brief, mice were anaesthetised with isoflurane, head-fixed in a stereotaxic frame and a 1 cm incision was performed on the scalp prior to craniotomy (coordinates AP = −1.9, ML = 3.0 from bregma).…”
Section: Methodsmentioning
confidence: 99%